The impact of liquidity on in ation-linked bonds: A hypothetical indexed bonds approach - Julia Auckenthaler; Alexander Kupfer; Rupert Sendlhofer (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
The sovereign's intention to issue inflation-linked bonds (ILB) is to save money. More than 15 years' experience with this financial instrument in the United States and in several other countries has led to the conclusion that these bonds are costly and basically characterized by low liquidity issues. Recently, various papers have started to analyze the impact of liquidity on ILB yields. This paper summarizes studies concerning ILB liquidity at a glance and adds a new estimation strategy of the liquidity premium based on Campbell & Shiller's (1996) hypothetical ILB yields. We calculate the difference between observed and hypothetical ILB yields, regress this time series on a set of ILB-specific liquidity as well as general market uncertainty measures and find statistically and economically significant effects of the liquidity measures for the United States, the United Kingdom and Canada.
Keywords: G12; G01; H63; 330; Inflation-linked bonds; liquidity; hypothetical yields